Motive for Social Justice and Students Activism at University Level - Serafimovska, Eleonora; Marijana Markovikj (European Journal of Social Science Education and Research, 2024)
Student organizations exist to protect the rights and interests of their members. Therefore, if they are organized into representative student governments, students can be a very influential agent who shapes the policy of higher education, and build themselves as democratic force in the society. The purpose of this study conducted by Institute for Sociological, Political and Juridical Research (ISPJR), Skopje was to consider student activism at university level in light of social justice motive. The data show that components of social justice motive influence the activism in Student Organization but also certainly proved that educational system of the country has serious omissions and errors in developing responsible and active youth and the country has to invest in its students because good student organization, in addition to exercising rights, freedoms and needs, and engaging in improving students’ standard and their well-being, means investing in an active, efficient, motivated and democratic youth.